2006
DOI: 10.1038/sj.ejcn.1602416
|View full text |Cite
|
Sign up to set email alerts
|

Diet among breast cancer survivors and healthy women. The Norwegian Women and Cancer Study

Abstract: Objective: To compare the diet and lifestyle in breast cancer survivors and healthy women. Design: Cross-sectional study in the population-based Norwegian Women and Cancer cohort study, using a postal questionnaire on diet, lifestyle and health. Setting: Nation-wide, population-based study. Subjects: Women aged 41-70 years. Prevalent breast cancer cases (314 short-term with 1-5 years since diagnosis, 352 longterm with 45 years since diagnosis) were identified by linkage to the Norwegian Cancer Registry. The co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
20
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
(54 reference statements)
4
20
1
Order By: Relevance
“…Higher supplement use among cancer survivors is consistent with literature (Rock et al, 2004;Molassiotis et al, 2005;Skeie et al, 2006;Velicer and Ulrich, 2008), despite the lack of evidence that it is an effective means of secondary (or primary) prevention of cancer (Bjelakovic et al, 2004;Huang et al, 2006;WCRF/AICR, 2007).…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Higher supplement use among cancer survivors is consistent with literature (Rock et al, 2004;Molassiotis et al, 2005;Skeie et al, 2006;Velicer and Ulrich, 2008), despite the lack of evidence that it is an effective means of secondary (or primary) prevention of cancer (Bjelakovic et al, 2004;Huang et al, 2006;WCRF/AICR, 2007).…”
Section: Discussionsupporting
confidence: 69%
“…Although the percentage of supplement users is higher among cancer survivors, for example, than in the general population (Rock et al, 2004;Skeie et al, 2006), much is unknown or poorly documented regarding the associations between supplement use and health (Huang et al, 2006;Bjelakovic et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, the decrease in vegetable intake was about 102 g/d (>1 serving of 80 g). Previous studies generally observed an increase in vegetable intake among cancer survivors 15, 20, 21, 22, 23, 24, 26, 28. However, most of them were based on qualitative and/or retrospective data.…”
Section: Discussionmentioning
confidence: 89%
“…Dietary and alcohol intakes of cancer survivors have received increasing attention in the last decade 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29. Overall, these studies tended to suggest an improvement in dietary behavior after cancer diagnosis, as well as a strong motivation of cancer survivors to make lifestyle changes 4.…”
Section: Introductionmentioning
confidence: 99%
“…11,15 Compared with healthy women, Norwegian breast cancer survivors did not have a significantly higher consumption of CLO, but used other dietary supplements at a higher frequency. 16 The difference was limited to those surveyed rather shortly (1-5 years) after diagnosis.…”
mentioning
confidence: 99%